Revealing novel and conservative CD8+T-cell epitopes with MHC B2 restriction on ALV-J - Xueqing Li; Ziwei Li; Mulin Ma; Na Yang; Shanyao Du; Ming Liao; Manman Dai (Veterinary Research)
Abstract MHC B2 haplotype chickens have been reported to induce strong immune response against various avian pathogens. However, little is known about the CD8+T-cell epitope with MHC B2-restricted on subgroup J avian leukosis virus (ALV-J). In this study, we explored the ALV-J-induced cellular immune response in B2 haplotype chickens in vivo. We found that ALV-J infection significantly increased the proportion of CD8+T cells in chickens and up-regulated the expression of cytotoxic genes like Granzyme A and antiviral genes like IFIT5 at 14 days post-infection (dpi). We selected 32 candidate peptides based on the peptide-binding motif and further identified three MHC B2-restricted CD8+T epitopes on ALV-J, including Pol652−660, Gag374−382, and Gag403−411 which induced significant levels of chicken IFN-γ production in splenocytes from ALV-J infected chickens using the ELISpot assay. In addition, we also verified that the three identified epitopes stimulated memory splenocytes elevating TNF-α and IL-2 protein expression. Importantly, we found that the three positive peptides were highly conserved among ALV-A, ALV-B, ALV-E, ALV-J, and ALV-K. Taken together, we identified three MHC B2-restricted CD8+T cell epitopes on ALV-J, providing a foundation for developing effective T cell epitope vaccines targeting conserved internal viral proteins.